Impact of non-fungible token digital art information on intention to purchase digital collectibles: an extended theory of planned behavior approach - Chung, Donghwa; Meng, Yanfang; Wang, Jiaqi (Frontiers in Communication, 2025)
BackgroundIn recent years, the rise of “AI+arts” has increased public attention towards emerging digital collectibles and garnered significant interest among young adult collectors globally. However, there has been limited investigation into how emerging media effects may influence consumers’ purchase of digital collectibles from the perspective of relevant theories, particularly in collectivistic cultural contexts. To address this gap, the present study is guided by the extended Theory of Planned Behavior (TPB), integrated with ideal self-congruence, and rigorously examines the effect of exposure to Non-Fungible Token digital art information on the intention to purchase digital collectibles among young Chinese adults (aged 18–34).MethodsA total of 259 responses were obtained through an online survey. Statistical analyses, including direct, indirect, and serial mediation, were conducted using SPSS 25.0 and Jamovi 2.6.24.ResultsThe findings indicate that both TPB and ideal self-congruence act as mediators in this relationship. Additionally, a serial mediation process involving ideal self-congruence and attitudes toward intelligence was identified.ConclusionThese findings provide valuable insights into the complex factors influencing the purchase intention of digital collectibles among young Chinese adults. Furthermore, the findings offer recommendations for digital collectible platforms and relevant stakeholders.